Potential of polyethylene terephthalate (PET) in a circular economy from a life cycle assessment perspective - a case study for anaesthesia and surgical instrument packaging waste in Australia - Keul, Constantin; Spierling, Sebastian; Venkatachalam, Venkateshwaran; Endres, Hans-Josef; Barner, Leonie; Wyssusek, Kerstin (Frontiers in Environmental Science, 2024)
Plastics are a versatile material group with many applications in the healthcare sector. Clinicians, particularly in the operating rooms, have become increasingly dependent on single-use instruments and consumables typically packaged in Polyethylene Terephthalate (PET) resulting in significant amounts of PET waste. In this study, a life cycle assessment (LCA) methodology based on ISO 14040/44 is conducted to assess the environmental impacts of existing and potential future end-of-life options for PET anaesthesia and surgical instrument packaging waste in an Australian hospital context. The results show the reduction potential of environmental impacts by recycling of PET waste via direct collection or in Materials Recovery Facility (MRF) in Australia, Indonesia and New Zealand. When replacing end-of-life options such as landfill or incineration with recycling, a reduction of 88% of total Climate Change (CC) impact can be seen. Furthermore, there is a reduction in environmental impacts across other impact categories through this change. Even if the recyclate quality (up to 30%) was reduced, there is a significant reduction in the environmental impacts. The transition of end-of-life options to recycling offers the potential for reduction of emissions and enables a circular economy for plastics. Furthermore, based on the results of LCA, opportunities and challenges of circular economy pathways in health industry are identified and discussed in this study.